1999
DOI: 10.1002/(sici)1096-8652(199906)61:2<139::aid-ajh12>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Fetal hemoglobin expression in the compound heterozygous state for ?117 (G?A)A? HPFH and IVSII-745 (C?G) ?+ thalassemia: A case study

Abstract: We studied a family in which two inherited defects of the non-␣-globin cluster segregate: Greek hereditary persistence of fetal hemoglobin (HPFH) and ␤-thalassemia. The compound heterozygote is a healthy man with 43% HbF, G ␥/ A ␥ ratio (27:73) differing from that of 10 simple heterozygotes for the Greek HPFH (92:8), normal levels of total Hb (13.3 g/dl), and reduced HbA 2 levels comparing with the levels of ␤-thal heterozygotes for the same mutation. Molecular analysis of the ␤-globin genotype revealed the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Patients bearing H ereditary P ersistence of F etal H emoglobin (HPFH) mutations have high levels of fetal γ-hemoglobin (HbF) that aberrantly persist into adulthood [3]. It has been observed clinically that the co-inheritance of an HPFH mutation in SCD patients significantly mitigates SCD symptoms [4][7]. Thus, for the past three decades, the scientific community has made concerted efforts to develop strategies by which we might safely and efficiently induce HbF synthesis in adult definitive erythroid cells as a potential therapy to treat SCD.…”
Section: Introductionmentioning
confidence: 99%
“…Patients bearing H ereditary P ersistence of F etal H emoglobin (HPFH) mutations have high levels of fetal γ-hemoglobin (HbF) that aberrantly persist into adulthood [3]. It has been observed clinically that the co-inheritance of an HPFH mutation in SCD patients significantly mitigates SCD symptoms [4][7]. Thus, for the past three decades, the scientific community has made concerted efforts to develop strategies by which we might safely and efficiently induce HbF synthesis in adult definitive erythroid cells as a potential therapy to treat SCD.…”
Section: Introductionmentioning
confidence: 99%
“…When haplotype IIIa was associated with the ␤-globin mutation combined with the XmnI site in-cis or in-trans (one case), or in the homozygous state, high HbF levels were measured. We have recently published [30] a case study from a Greek family, where one of the individus had co-inherited in-trans the IVSII-745 (C→G) ␤ + thalassaemia with the G ␥ −158 C→T. This double heterozygote presented HbF levels 3.7%, with a G ␥/ A ␥ ratio 69/31.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, it seems this particular deletion is linked to the normal b-globin gene in the majority of individuals with normal Hb F levels. However, other studies have reported a reduction of A g-globin gene production in individuals with this 4 bp deletion (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%